An exploration into customer perception of sustainable attributes in alternate primary and secondary markets - Bhardwaj, Munisha (2017)
The following dissertation is based around exploring customer perception in regards to sustainability in both primary and secondary markets. The study has been driven from the rise of environmental concerns and how businesses and social groups are trying to expand consumer base and encourage more consumers to be more aware and ecological. Therefore, this study aims to explore current consumer perception and knowledge around sustainability, and understand how important this attribute is to the individual when purchasing a high involvement good. The research will involve primary (first hand) and secondary (second hand) consumers, in order to gain a more valid data collection of different types of purchasers.